PENGARUH INFRASTRUKTUR TERHADAP PERTUMBUHAN EKONOMI KABUPATEN FAKFAK PROVINSI PAPUA BARAT - Risma Niswati Tarman; Herdy Pratama Putra; Ahfandi Ahmad (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Infrastructure is basically a government asset that is built in the context of serving the community. Road and electricity infrastructure have a large, positive and significant influence on economic growth without exception in Fakfak Regency, West Papua. So that it can determine the direction of government policy in infrastructure development that is in accordance with the conditions in Fakfak Regency. This study aims (1) to determine the effect of roads on economic growth in Fakfak District (2) to determine the effect of electricity on economic growth in Fakfak District. This research is a quantitative descriptive study using panel data regression analysis from 2017 to 2021 in Fakfak district. The objects studied include (1) GRDP (economic growth) (2) Infrastructure consisting of: road infrastructure and electricity infrastructure.Keywords: Infrastructure, Panel Data, Growth, Fakfak.